2020
DOI: 10.1108/raf-10-2019-0221
|View full text |Cite
|
Sign up to set email alerts
|

Annual report readability and trade credit

Abstract: Purpose The purpose of this study is to examine the influence of the readability of annual reports on firms’ ability to obtain trade credit from suppliers. Particularly, the authors conjecture that annual report readability helps firms obtain more trade credit from suppliers. Design/methodology/approach The authors use the Gunning Fog Index as the primary measure of annual report readability and the ratio of accounts payable to the book value of total assets as the measure of trade credit. Findings Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…Consequently, trade creditors are likely to react louder than banks to voluntary disclosure since they do not ask usually for private information from their customers to keep their trust relationship. In the same vein, the results of Xu et al (2020) indicate that firms with more readable annual reports are likely to benefit from more trade credit.…”
Section: Risk Disclosure Literaturementioning
confidence: 95%
See 4 more Smart Citations
“…Consequently, trade creditors are likely to react louder than banks to voluntary disclosure since they do not ask usually for private information from their customers to keep their trust relationship. In the same vein, the results of Xu et al (2020) indicate that firms with more readable annual reports are likely to benefit from more trade credit.…”
Section: Risk Disclosure Literaturementioning
confidence: 95%
“…No study has investigated this issue, to the best of the authors' knowledge. Recently, few researchers start investigating the association between trade credit and disclosure in general and particularly annual report readability (Xu et al 2020) or voluntary disclosure (Ceustermans et al 2017). For instance, Ceustermans et al (2017) found that voluntary disclosure is positively related to the level of trade credit for small and private companies.…”
Section: Risk Disclosure Literaturementioning
confidence: 99%
See 3 more Smart Citations